Under the volcano : a novel - Lowry, Malcolm, 1909-1957. (New York : Harper/Perennial, 2007)
Alcoholic consul Geoffrey Firmin's life changes over the course of one day when his wife Yvonne arrives in Mexico on a mission to save him and their failing marriage.
Originally published in 1947.
Adult.
Adult
Keywords: Alcoholics -- Fiction; All Souls' Day -- Fiction; British -- Mexico -- Fiction; Consuls -- Fiction; Alcoholics -- Fiction; All Souls' Day -- Fiction; Diplomats -- Fiction; Psychological fiction; Cuernavaca (Mexico) -- Fiction; Cuernavaca (Mexico) -- Fiction; Mexico -- Fiction; Psychological fiction